EKSISTENSI KAJIAN GREEN PARTY DALAM PARTAI POLITIK DI INDONESIA - Apriyani, Sinta; Lestari, Vivi (Jurnal Analisis Sosial Politik, 2023)
Political parties that care about the environment and are actualized in the vision-mission and program of their political party activities must be fought for the future. The form of political awareness of the environment or what is then referred to as green politics in Indonesia until now is implemented in a green party by submitting petitions, lawsuits over policies and mass mobilization actions to pay attention to ecological aspects. The method in this study uses a literature review. Data sources use secondary data sources in the form of documents, laws and regulations, articles and books. The issue of environmental justice has been realized from a community and government support towards something that must be on the platform of political parties. The current reality related to the green political narrative that can be judged from the various political promises of candidates from political parties ahead of the general election and the vision and mission of political party programs has not been fully realized and only beautiful on paper the existence of Green Politics in Indonesia is needed.